Two‐dimensional and three‐dimensional models for studying atherosclerosis pathogenesis induced by periodontopathogenic microorganisms (2018)
Epidemiological studies have established a clinical association between periodontal disease and atherosclerosis. Bacteremia and endotoxemia episodes in patients with periodontitis appear to link these two diseases by inducing a body‐wide production of cardiovascular markers. The presence of oral bacteria in atherosclerotic lesions in patients with periodontitis suggests that bacteria, or their antigenic components, induce alterations in the endothelium associated with atherosclerosis. Therefore, a causal mechanism explaining the association between both diseases can be constructed using in vitro models. This review presents current experimental approaches based on in vitro cell models used to shed light on the mechanism by which periodontal pathogenic microorganisms, and their antigenic components, induce proatherosclerotic endothelial activity. Monolayer cultures of endothelial vascular or arterial cells have been used to assess periodontal pathogenic bacteria and their antigenic compounds and endothelial activation. However, these models are not capable of reflecting the physiological characteristics of the endothelium inside vascularized tissue. Therefore, the shift from two‐dimensional (2D) cellular models toward three‐dimensional (3D) models of endothelial cells resembling an environment close to the physiological environment of the endothelial cell within the endothelium is useful for evaluating the physiological relevance of results regarding the endothelial dysfunction induced by periodontopathogens that are currently obtained from 2D models. The use of in vitro 3D cellular models can also be relevant to the search for therapeutic agents for chronic inflammatory diseases such as atherosclerosis. Here, we present some strategies for the assembly of 3D cultures with endothelial cells, which is useful for the study of periodontopathogen‐mediated disease.